Rhododendron Arboreum Phytochemistry, Medicinal Applications and Pharmacology: A Review - Shubhi Agarwal; Anurita Rajput (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Rhododendron is a tiny evergreen tree with deep red or pastel pink blossoms from the Ericaceae family. The species is extensively distributed between 80°N and 20°S and is the national flower of Nepal and state flower of Himachal Pradesh (India). Besides its horticultural function, it's utilized as an attractive plant in gardens, roadways, and vessels. Because of its phytochemical potential, it's used to treat ailments. Mountain people use this plant's flowers to create pickle, juice, jam, syrup, honey, squash, etc., and to treat diarrhoea, headache, and inflammation, bacterial and fungal illnesses. The present review highlights Rhododendron's medicinal, nutritional, and prospective capabilities by developing value-added goods to improve the rural tribal population's livelihood and work chances.